Temperature in the railway disc brake at a repetitive short-term mode of braking. (May 2017) - Yevtushenko, A.A.; Kuciej, M.; Grzes, P.; Wasilewski, P.
Abstract: The finite element (FE) model to determine the transient temperature field in the ventilated disc brake of the traction diesel multiple unit (DMU) has been proposed. The advantage of the developed numerical model is the representation of mutual motion of the stationary pad and the rotating disc, by a heat source of arbitrary shape moving over the stationary disc. Computations were carried out for the pad and the disc separately introducing the heat partition ratio. Both the single and the multiple modes of braking were examined. The calculated distributions in contact temperature were compared with the corresponding results obtained from analytical solutions of the boundary-value thermal problem of friction, and with experimental data determined by the method of thermocouples. It was demonstrated that the calculated mean temperature on the friction surfaces of the brake components and the bulk temperature of the disc during multiple brake application agree well with the corresponding results, obtained by methods mentioned above.